A natural stone thermal insulation decorative integrated board based on microcrystalline foamed ceramics and a preparation method thereof
By adding modified epoxy resin stone AB glue between the natural stone layer and the foamed ceramic layer, and adding high-hardness granite and other materials to the foamed ceramics to form an integrated structure, the problems of high brittleness and poor insulation performance of existing foamed ceramic sheets are solved, and the hardness and insulation performance of the material are significantly improved.
Patent Information
- Application Number
- CN202211142193.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-20
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2042-09-20
AI Technical Summary
The existing foamed ceramic sheets are highly brittle, fragile, and have poor thermal insulation performance, making it difficult to significantly improve the energy-saving effect of buildings.
The natural stone insulation decorative integrated panel based on microcrystal foamed ceramics is used. By adding modified epoxy resin stone AB glue between the natural stone layer and the foamed ceramic layer, an integrated structure is formed, and high-hardness granite, ceramic scraps, clay, hollow microbeads and other materials are added to the foamed ceramics to improve its hardness and insulation properties.
While reducing construction processes and costs, the hardness and insulation properties of the material are significantly improved, the thermal conductivity is reduced, the water absorption rate and apparent density are also optimized, and the compressive strength reaches more than 7MPa.
Smart Images

Figure 308529DEST_PATH_IMAGE001
Abstract
Description
Technical Field
[0001] The invention relates to the field of foamed ceramics and thermal insulation materials, and in particular to a natural stone thermal insulation and decorative integrated board based on microcrystalline foamed ceramics and a preparation method thereof. Background Art
[0002] Foamed ceramic insulation integrated board is suitable for building exterior wall insulation, fire isolation zone, building self-insulation cold and hot bridge treatment, etc. Foamed ceramic refers to a ceramic product with closed holes inside. It is lightweight, soundproof and heat-insulating, and is a good masonry insulation material. The conventional practice of producing this material is to add a foaming agent to the ceramic body formula. The foaming agent produces gas during the high-temperature sintering process. These gases are wrapped by the liquid phase produced by the high-temperature sintering. After cooling, honeycomb-shaped closed pores are formed inside the body. It has good compatibility with the wall base and plastering layer, good safety and stability, and can have the same lifespan as the building. More importantly, the material has an A1 fireproof grade, which overcomes the fatal weaknesses of thermal insulation materials such as rock wool and organic materials, which are easy to age and afraid of open flames, and fills the domestic gap in inorganic thermal insulation materials for buildings.
[0003] Although foamed ceramic panels have good fireproofing, sound insulation, and heat preservation advantages, they are generally used for building exterior walls. However, foamed ceramic panels are brittle and easily break when they collide. Existing foamed ceramic panels need to be sprayed with a layer of spray paint or sintered with a layer of finishing layer when they are used to protect the surface of the foamed ceramic panels and increase their surface ornamental properties. However, the surface of the foamed ceramic panels sprayed in the spraying method is easily broken after a collision, and the method of sintering a finishing layer is complicated and costly. At the same time, the existing foamed ceramic panels have poor thermal insulation performance and have no obvious energy-saving effect on buildings. Summary of the invention
[0004] In order to overcome the above technical problems, the object of the present invention is to provide a natural stone thermal insulation and decorative integrated board based on microcrystalline foamed ceramics and a preparation method thereof.
[0005] The technical solutions adopted are:
[0006] A natural stone thermal insulation decorative integrated board based on microcrystalline foamed ceramic and a preparation method thereof, characterized in that it comprises a natural stone layer, an unsaturated resin adhesive layer and a foamed ceramic layer, the stone layer adopts natural limestone, one side of the stone layer is an unsaturated resin adhesive layer, one side of the unsaturated resin adhesive layer is a foamed ceramic layer, the foamed ceramic layer comprises 50-70% of granite tailings, 10-20% of ceramic scraps, 5-15% of clay, 5-10% of hollow microspheres, 1-10% of flux, 1-10% of foaming agent, 0.5-2% of stabilizer, 1-3% of binder and some water.
[0007] Preferably, the stone layer is made of natural limestone with a thickness of 10-15 mm.
[0008] Preferably, the unsaturated resin adhesive layer uses modified epoxy resin stone AB adhesive with a solid content of >95% and an A:B ratio of 2:1.
[0009] Preferably, the binder is yellow dextrin.
[0010] The natural stone thermal insulation decorative integrated board based on microcrystalline foamed ceramics and the preparation method thereof described in any of the above schemes are characterized by comprising the following steps:
[0011] S1 Preparation of stone layer: Cut natural limestone into 10-15mm stones, polish and grind on one side, and roughen on the other side;
[0012] S2 Preparation of foamed ceramics:
[0013] (1) Pretreatment of raw materials
[0014] After the surface of granite tailings and ceramic scraps is cleaned, they are crushed into particles with a particle size of less than 1mm using a jaw crusher. Granite tailings particles, steel grinding balls and water are loaded into a pot mill in a mass ratio of 1:1:1, and the ball milling time is 3-5h, the speed is 60-120 r / min, and the obtained slurry is filtered, precipitated, dried, and crushed to obtain granite tailings and ceramic scraps fine powder; the clay powder is placed in an oven (110±5℃) and dried for 24-48h, and sieved with a 200-mesh standard sieve to obtain dry clay fine powder with a particle size of less than 0.075mm;
[0015] (2) Weighing and mixing of raw materials
[0016] Weigh the powders according to the ratio requirements, including granite tailings, ceramic scraps, clay and foaming agent. Put the above powders into the polyurethane ball mill together, and then weigh the corundum grinding balls and water according to the mass ratio of powder: corundum grinding balls: water = 1:1:1.5, and put them into the ball mill, and mix them in a planetary ball mill for 1-2 hours at a speed of 300-400 r / min. After filtering the mixed slurry, transfer it to an oven (110±5℃) and dry it for 12-24 hours, then crush it into powder, add hollow microbeads, flux, stabilizer, and binder and mix evenly to obtain a mixture, which is put into the ball mill together and mixed for 2-4 hours. The filtered slurry is transferred to a mold and sent to a drying oven (110±5℃) to dry for 12-24 hours;
[0017] (3) Firing of foamed ceramics
[0018] The treated mixture is transferred to a high temperature furnace together with the mold, and fired at a temperature of 1150-1250°C in an air atmosphere, and then cooled to room temperature with the furnace to obtain a foamed ceramic;
[0019] S3 Preparation of natural stone thermal insulation and decorative integrated panels based on microcrystalline foamed ceramics:
[0020] The foamed ceramic prepared by S2 is cut into pieces with a thickness of 20-50 mm, and the modified epoxy resin stone AB glue is mixed in a ratio of 2:1 and evenly applied to the rough surface of the S1 stone, and then bonded and fixed with the cut foamed ceramic for 2.5 hours to obtain a natural stone thermal insulation and decorative integrated board based on microcrystalline foamed ceramic.
[0021] The beneficial effects of the present invention are:
[0022] 1. The present invention uses modified epoxy resin stone AB glue to integrate natural stone decorative materials with foamed ceramics, which can reduce the process of additional decoration after the exterior wall is pasted with thermal insulation materials. This not only reduces the construction process and saves a lot of costs, but also greatly reduces the difficulty of construction;
[0023] 2. The foamed ceramic of the present invention not only uses high-hardness granite as the main raw material to improve its hardness and compressive strength, but also adds high-temperature resistant hollow microspheres to improve its thermal insulation performance. Its thermal conductivity is less than 0.065W / (m·k), water absorption is less than 0.5%, and apparent density is less than 0.48 g / cm 3 , the compressive strength is above 7MPa. DETAILED DESCRIPTION
[0024] The present invention is described in detail below through specific examples, but the use and purpose of these exemplary implementation modes are only used to illustrate the present invention, and do not constitute any form of limitation on the actual protection scope of the present invention, nor limit the protection scope of the present invention to them.
[0025] In addition, unless otherwise specified, the percentages used in the following components are all percentages by weight.
[0026] Example 1
[0027] A natural stone thermal insulation and decorative integrated board based on microcrystalline foamed ceramics and a preparation method thereof, characterized in that it comprises a natural stone layer, an unsaturated resin adhesive layer and a foamed ceramic layer, the stone layer adopts natural limestone, one side of the stone layer is an unsaturated resin adhesive layer, one side of the unsaturated resin adhesive layer is a foamed ceramic layer, the foamed ceramic layer comprises 70% of granite tailings, 10% of ceramic scraps, 5% of clay, 5% of hollow microspheres, 2% of flux, 3% of foaming agent, 0.5% of stabilizer, 1% of binder and some water.
[0028] The natural stone thermal insulation decorative integrated board based on microcrystalline foamed ceramic using the above raw materials and the preparation method thereof include the following steps:
[0029] S1 Preparation of stone layer: natural limestone is cut into 15 mm stones, one side is polished and the other side is roughened;
[0030] S2 Preparation of foamed ceramics:
[0031] (1) Pretreatment of raw materials
[0032] After the surface of granite tailings and ceramic scraps is cleaned, they are crushed into particles with a particle size of less than 1mm using a jaw crusher. Granite tailings particles, steel grinding balls and water are loaded into a pot mill in a mass ratio of 1:1:1, ball milling time is 3h, speed is 80 r / min, the obtained slurry is filtered, precipitated, dried, and crushed to obtain granite tailings and ceramic scraps fine powder; the clay powder is placed in an oven (110±5℃) and dried for 24h, and sieved with a 200-mesh standard sieve to obtain dry clay fine powder with a particle size of less than 0.075mm;
[0033] (2) Weighing and mixing of raw materials
[0034] Weigh the powders according to the ratio requirements, including granite tailings, ceramic scraps, clay and foaming agent. Put the above powders into the polyurethane ball mill together, and then weigh the corundum grinding balls and water according to the mass ratio of powder: corundum grinding balls: water = 1:1:1.5, and put them into the ball mill, and mix them in a planetary ball mill for 1 hour at a speed of 300r / min. After filtering the mixed slurry, transfer it to an oven (110±5℃) and dry it for 12 hours, then crush it into powder, and then add hollow microbeads, flux, stabilizer, and binder to mix evenly to obtain a mixture, which is put into the ball mill together and mixed for 2 hours. The filtered slurry is transferred to a mold and sent to a drying oven (110±5℃) to dry for 12 hours;
[0035] (3) Firing of foamed ceramics
[0036] The treated mixture is transferred to a high temperature furnace together with the mold, and fired at a temperature of 1150°C in an air atmosphere, and then cooled to room temperature with the furnace to obtain a foamed ceramic.
[0037] S3 Preparation of natural stone thermal insulation and decorative integrated panels based on microcrystalline foamed ceramics:
[0038] The foamed ceramic prepared by S2 was cut into pieces with a thickness of 20 mm, and the modified epoxy resin stone AB glue was mixed in a ratio of 2:1 and evenly applied to the rough surface of the S1 stone, and then bonded and fixed with the cut foamed ceramic for 2.5 hours to obtain a natural stone thermal insulation and decorative integrated board based on microcrystalline foamed ceramic.
[0039] Example 2
[0040] A natural stone thermal insulation and decorative integrated board based on microcrystalline foamed ceramics and a preparation method thereof, characterized in that it comprises a natural stone layer, an unsaturated resin adhesive layer and a foamed ceramic layer, the stone layer adopts natural limestone, one side of the stone layer is an unsaturated resin adhesive layer, one side of the unsaturated resin adhesive layer is a foamed ceramic layer, the foamed ceramic layer comprises 65% of granite tailings, 15% of ceramic scraps, 10% of clay, 7% of hollow microspheres, 4% of flux, 4% of foaming agent, 1% of stabilizer, 2% of binder and some water.
[0041] The natural stone thermal insulation decorative integrated board based on microcrystalline foamed ceramic using the above raw materials and the preparation method thereof include the following steps:
[0042] S1 Preparation of stone layer: natural limestone is cut into 15 mm stones, one side is polished and the other side is roughened;
[0043] S2 Preparation of foamed ceramics:
[0044] (1) Pretreatment of raw materials
[0045] After the surface of granite tailings and ceramic scraps is cleaned, they are crushed into particles with a particle size of less than 1mm using a jaw crusher. Granite tailings particles, steel grinding balls and water are loaded into a pot mill in a mass ratio of 1:1:1, ball milling time is 4h, speed is 100r / min, the obtained slurry is filtered, precipitated, dried, and crushed to obtain granite tailings and ceramic scraps fine powder; the clay powder is placed in an oven (110±5℃) and dried for 36h, and sieved with a 200-mesh standard sieve to obtain dry clay fine powder with a particle size of less than 0.075mm;
[0046] (2) Weighing and mixing of raw materials
[0047] Weigh the powders according to the ratio requirements, including granite tailings, ceramic scraps, clay and foaming agent. Put the above powders into the polyurethane ball mill together, and then weigh the corundum grinding balls and water according to the mass ratio of powder: corundum grinding balls: water = 1:1:1.5, and put them into the ball mill, and mix them in a planetary ball mill for 1.5 hours at a speed of 350r / min. After filtering the mixed slurry, transfer it to an oven (110±5℃) and dry it for 18 hours, then crush it into powder, and then add hollow microbeads, flux, stabilizer, and binder to mix evenly to obtain a mixture, which is put into the ball mill together and mixed for 3 hours. The filtered slurry is transferred to a mold and sent to a drying oven (110±5℃) to dry for 18 hours;
[0048] (3) Firing of foamed ceramics
[0049] The treated mixture is transferred to a high temperature furnace together with the mold, and fired at a temperature of 1200°C in an air atmosphere, and then cooled to room temperature with the furnace to obtain a foamed ceramic.
[0050] S3 Preparation of natural stone thermal insulation and decorative integrated panels based on microcrystalline foamed ceramics:
[0051] The foamed ceramic prepared by S2 was cut into pieces with a thickness of 20 mm, and the modified epoxy resin stone AB glue was mixed in a ratio of 2:1 and evenly applied to the rough surface of the S1 stone, and then bonded and fixed with the cut foamed ceramic for 2.5 hours to obtain a natural stone thermal insulation and decorative integrated board based on microcrystalline foamed ceramic.
[0052] Example 3
[0053] A natural stone thermal insulation and decorative integrated board based on microcrystalline foamed ceramics and a preparation method thereof, characterized in that it comprises a natural stone layer, an unsaturated resin adhesive layer and a foamed ceramic layer, the stone layer adopts natural limestone, one side of the stone layer is an unsaturated resin adhesive layer, one side of the unsaturated resin adhesive layer is a foamed ceramic layer, the foamed ceramic layer comprises 50% of granite tailings, 20% of ceramic scraps, 15% of clay, 10% of hollow microspheres, 5% of flux, 6% of foaming agent, 1.5% of stabilizer, 2.5% of binder and some water.
[0054] The natural stone thermal insulation decorative integrated board based on microcrystalline foamed ceramic using the above raw materials and the preparation method thereof include the following steps:
[0055] S1 Preparation of stone layer: natural limestone is cut into 15 mm stones, one side is polished and the other side is roughened;
[0056] S2 Preparation of foamed ceramics:
[0057] (1) Pretreatment of raw materials
[0058] After the surface of granite tailings and ceramic scraps is cleaned, they are crushed into particles with a particle size of less than 1mm using a jaw crusher. Granite tailings particles, steel grinding balls and water are loaded into a pot mill at a mass ratio of 1:1:1, ball milling time is 5 hours, speed is 120r / min, the obtained slurry is filtered, precipitated, dried, and crushed to obtain granite tailings and ceramic scraps fine powder; the clay powder is placed in an oven (110±5℃) and dried for 48 hours, and sieved with a 200-mesh standard sieve to obtain dry clay fine powder with a particle size of less than 0.075mm;
[0059] (2) Weighing and mixing of raw materials
[0060] Weigh the powders according to the ratio requirements, including granite tailings, ceramic scraps, clay and foaming agent. Put the above powders into the polyurethane ball mill together, and then weigh the corundum grinding balls and water according to the mass ratio of powder: corundum grinding balls: water = 1:1:1.5, and put them into the ball mill, and mix them in a planetary ball mill for 2 hours at a speed of 400r / min. After filtering the mixed slurry, transfer it to an oven (110±5℃) and dry it for 12-24 hours, then crush it into powder, and then add hollow microbeads, flux, stabilizer, and binder to mix evenly to obtain a mixture, which is put into the ball mill together and mixed for 4 hours. The filtered slurry is transferred to a mold and sent to a drying oven (110±5℃) to dry for 24 hours;
[0061] (3) Firing of foamed ceramics
[0062] The treated mixture is transferred to a high temperature furnace together with the mold, fired at 1250°C in an air atmosphere, and cooled to room temperature to obtain a foamed ceramic.
[0063] S3 Preparation of natural stone thermal insulation and decorative integrated panels based on microcrystalline foamed ceramics:
[0064] The foamed ceramic prepared by S2 was cut into pieces with a thickness of 20 mm, and the modified epoxy resin stone AB glue was mixed in a ratio of 2:1 and evenly applied to the rough surface of the S1 stone, and then bonded and fixed with the cut foamed ceramic for 2.5 hours to obtain a natural stone thermal insulation and decorative integrated board based on microcrystalline foamed ceramic.
[0065] The foamed ceramics prepared in S2 of Examples 1-3 were tested. The test results are shown in Table 1 below.
[0066] Table 1 Performance test of foamed ceramics
[0067]
[0068] The closed-cell foamed ceramic prepared from the granite tailings as the main raw material in Examples 1-3 has a thermal conductivity of <0.065 W / (m·k), a water absorption rate of <0.5%, and an apparent density of <0.48 g / cm 3 , the compressive strength is above 7MPa, and it has great application potential in the field of decorative thermal insulation materials.
[0069] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.
Claims
1. A method for preparing a natural stone thermal insulation decorative integrated board based on microcrystalline foamed ceramics, characterized in that: The steps include: S1 Preparation of stone layer: Cut natural limestone into 10-15mm stones, polish and grind on one side, and roughen on the other side; S2 preparing a foamed ceramic layer, wherein the foamed ceramic layer comprises 50-70% of granite tailings, 10-20% of ceramic scraps, 5-15% of clay, 5-10% of hollow microspheres, 1-10% of flux, 1-10% of foaming agent, 0.5-2% of stabilizer, 1-3% of binder and some water; The specific preparation method of the foamed ceramic layer is as follows: (1) Pretreatment of raw materials After the surface of granite tailings and ceramic scraps are cleaned, they are crushed into particles with a size of less than 1mm using a jaw crusher; Granite tailing particles, steel grinding balls and water are loaded into a pot mill in a mass ratio of 1:1:1, and the ball milling time is 3-5 hours, and the rotation speed is 60-120r / min. The obtained slurry is filtered, precipitated, dried, and crushed to obtain granite tailing and ceramic scrap fine powder; the clay powder is placed in an oven for drying for 24-48 hours, the oven temperature is 110±5℃, and sieved with a 200-mesh standard sieve to obtain dry clay fine powder with a particle size of less than 0.075mm; (2) Weighing and mixing of raw materials Weigh the powder materials according to the proportion requirements, including granite tailings, ceramic scraps, clay and foaming agent; Put the above powders into a polyurethane ball mill together, weigh corundum grinding balls and water according to the mass ratio of powder: corundum grinding balls: water = 1:1:1.5, put them into the ball mill, and mix them in a planetary ball mill for 1-2 hours at a speed of 300-400r / min; The mixed slurry is filtered and transferred to an oven for drying for 12-24 hours at a temperature of 110±5°C, then crushed into powder, hollow microspheres, flux, stabilizer, and binder are added and mixed evenly to obtain a mixture, which is then put into a ball mill for mixing for 2-4 hours. The filtered slurry is transferred to a mold and sent to a drying oven for drying for 12-24 hours at a temperature of 110±5°C. (3) Firing of foamed ceramics The treated mixture is transferred to a high temperature furnace together with the mold, and fired at a temperature of 1150-1250°C in an air atmosphere, and then cooled to room temperature with the furnace to obtain a foamed ceramic; S3 Preparation of natural stone thermal insulation and decorative integrated panels based on microcrystalline foamed ceramics: The foamed ceramic prepared by S2 is cut into pieces with a thickness of 20-50 mm, and the modified epoxy resin stone AB glue is mixed in a ratio of 2:1 and evenly applied to the rough surface of the S1 stone, and then bonded and fixed with the cut foamed ceramic for 2.5 hours to obtain a natural stone thermal insulation and decorative integrated board based on microcrystalline foamed ceramic.
2. The preparation method according to claim 1, characterized in that: The solid content of the modified epoxy resin stone AB glue in step S3 is >95%.
3. The preparation method according to claim 1, characterized in that: The binder in step S2 is yellow dextrin.
4. A natural stone thermal insulation and decorative integrated board based on microcrystalline foamed ceramics, characterized in that: A natural stone thermal insulation and decorative integrated board prepared by the preparation method described in any one of claims 1 to 3.
Citation Information
Patent Citations
Foamed ceramic prepared by using granite saw mud as base material and preparation method thereof
CN112759417A
Foamed ceramic and natural stone composite board
CN202401715U